Organizational-based resources as determinants of nurses’ job performance in Malaysia : the mediating role of motivation - Aizzat Mohd Nasurdin,; Tan, Cheng Ling; Sabrina Naseer Khan, (Penerbit Universiti Kebangsaan Malaysia, 2022)
In a healthcare setting, nurses are the majority of healthcare specialists, thus making their job performance the key determinant of patient’s care quality. Given the rising number of patients being admitted to public hospitals and the increasing demands imposed by patients and their higher expectations, the need to further improve nurses' performance and quality of service delivery becomes imperative. The Conservation of Resources (COR) theory is used to investigate the influence of human resource management methods (HRMPs), which represent organizational-based resources (in the form of participation and compensation) on nurses’ job performance (task performance and contextual performance) with motivation as the mediator. Partial Least Squares (PLS) technique was used to analyse the data collected from 354 nurses attached with Malaysian public hospitals. The results disclosed that both HRMPs have direct and positive effects on motivation. Similarly, motivation mediated the link between involvement and compensation with task and contextual performance. Similarly, motivation mediated the link between involvement and compensation with task and contextual performance. This study has offered a vital recommendation to the nurse supervisors to motivate the nurses by giving more prospects for them to engage in making decisions and participating in hospital affairs.